THE ESSENCE OF SAVING RANGA-DRAMA THEATRES - Basusab, Bullannavar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Indian art and artists through their wonderful performances have been drawing audience in a large number. Entertainment holds a significant place in human life, serving as a source of relaxation, enjoyment, and relief from the demands of daily routines. Hence the theatre goers have been mesmerized and attracted, especially the world of folk theatre and dances., spectacles have grown popular. Though theatres in Kannada with its ancient history have been recognized as professional and amateur theatres, the contribution of rural theatres still remains immense in the folk art theatre. Kannada theatres have a rich history as old as human civilization. Later it became a polite theatre with the culture of modernity. If Sanskrit plays are the inspiration for this polite theatre, then only the folk theatre can defend the essence of our soil in the desi heritage. From the confluence of these two, Career theatre emerged." The Bayalatas were created based on the original mythological epics and based on the original mythological epics and based on the historical material. Shakespeare Kandagal Hanamantaraya gave a vision to the professional organizations in this part with his plays. The Bayalata that followed the two paths of professional amateurs followed the path of Moodalapaya and Paduvalapaya as theatre-rich. From the theatre Puranas and Epics, the main plot was formed. Taking life in the present context and keeping entertainment as well as mental development as a landmark, the art of theatre is a testimony of vitality.